Mechanisms of language change in a functional system: the recent semantic evolution of English future time expressions - Nesselhauf, Nadja (Journal of historical linguistics, 2012)
In this paper, the semantic developments of the major future time expressions in Late Modern English are traced in detail, with the aim of uncovering mechanisms of language change in a complex functional system. The results of the study reveal that to express a pure prediction, the major shift that has taken place in the Late Modern period is from a comparatively frequent use of shall to a comparatively frequent use of ’ll; that to express a prediction based on the intention of the subject, BE going to and the present progressive have replaced will and shall to a certain degree; and that to express a prediction based on a previous arrangement, earlier uses of the simple present have been replaced to a considerable degree by the progressive with future time reference. In addition, the construction WANT to is identified as what may be called an emerging future marker, which has started to be used for predictions based on the subject’s intention. Finally, the possible contribution of certain stylistic and socio-cultural changes to the many recent changes in the system of English future time expressions is also considered, such as the complexification of society, (pseudo-)democratization, and a tendency of many text types towards a more personal style.
Gesehen am 15.08.2022